2018
DOI: 10.1093/chromsci/bmx113
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Estimation, Ex vivo Everted Sac Permeability and In Vivo Pharmacokinetic Studies of Darunavir

Abstract: Darunavir ethanolate (DRV) is an efficient protease inhibitor (PI) used in the treatment of human immunodeficiency virus (HIV) type-1 patients. An isocratic reversed-phase HPLC method was developed to monitor concentration of darunavir in in vitro intestinal fluid samples in everted sac absorption model in the presence of bioenhancers, viz., piperine, quercetin, naringenin. The method was validated and successfully applied to everted sac and pharmacokinetic studies in rats. The absorption profiles of DRV and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The interactions described for the animal studies in most cases also resulted in increased bioavailability (increased serum/plasma C max and/or increased AUC values) of the investigated drugs. However, interactions in animal studies were observed with several additional drugs, such as ibuprofen, nimesulide, oxyphenylbutazone (non-steroidal anti-inflammatory drugs); amoxycillin, ampicillin, norfloxacin, marbofloxacin, metronidazole (antibiotic drugs); glimepiride, nateglinide (antidiabetic drugs); simvastatin, rosuvastatin (lipid-lowering drugs); verapamil, diltiazeme (calcium channel blockers); sodium valproate (antiepileptic drug); darunavir ethanolate (HIV protease inhibitor); losartan (angiotensin II receptor type 1 antagonist); domperidone (antiemetic drug); almotriptan (anti-migraine drug); and fexofenadine (antihistaminic drug) [126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144].…”
Section: Interactions Of Piperine With Medicinal Products and Other Substancesmentioning
confidence: 99%
“…The interactions described for the animal studies in most cases also resulted in increased bioavailability (increased serum/plasma C max and/or increased AUC values) of the investigated drugs. However, interactions in animal studies were observed with several additional drugs, such as ibuprofen, nimesulide, oxyphenylbutazone (non-steroidal anti-inflammatory drugs); amoxycillin, ampicillin, norfloxacin, marbofloxacin, metronidazole (antibiotic drugs); glimepiride, nateglinide (antidiabetic drugs); simvastatin, rosuvastatin (lipid-lowering drugs); verapamil, diltiazeme (calcium channel blockers); sodium valproate (antiepileptic drug); darunavir ethanolate (HIV protease inhibitor); losartan (angiotensin II receptor type 1 antagonist); domperidone (antiemetic drug); almotriptan (anti-migraine drug); and fexofenadine (antihistaminic drug) [126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144].…”
Section: Interactions Of Piperine With Medicinal Products and Other Substancesmentioning
confidence: 99%
“…The protease enzyme is responsible for the breaking of HIV encoded Gag-Pol protein in a host cell infected with a virus and leads to the formation of the mature infectious viral particles. [8][9][10] For the effective management of HIV-1 infection, darunavir is administered with other PIs. The co-administration of cytochrome P450 enzyme inhibitor (ritonavir) with darunavir, there is a significant decrease in the viral load and enhanced Analytical method development is a crucial step in product development and the validation of the developed methods as per the guidelines ensures the suitability of the method for intended purpose.…”
Section: Crasmentioning
confidence: 99%